Right to inclusive education for children with disabilities at stake in Lithuania - Ruškus, Jonas (Special Education, 2020)
Since 2010 Lithuania is a State Party of the Convention on the Rights of Persons with Disabilities of the United Nations. The development of education policy in Lithuania as concerns the right to inclusive education for children with disabilities is analysed as well as the factual trends of education of children with disabilities in segregated and regular educational settings. Author explores the assumption that intersection of the patterns of medical model of and neoliberal mindset in educational discourse impedes the implementation of human rights standards, reasonable accommodation particularly.
Keywords: Lithuania; Inclusive education; Disability; Convention on the Right of Persons with disabilities of the United Nations; Reasonable accommodation